Influência da apoptose na resistência hepática e esplênica de cães com leishmaniose visceral - Moreira, Pamela Rodrigues Reina [UNESP]; Franciscato, Douglas Augusto [UNESP]; Rossit, Sabrina Micelli [UNESP]; Munari, Danísio Prado [UNESP]; Vasconcelos, Rosemeri de Oliveira [UNESP] (FapUNIFESP (SciELO), 2016)
The aim of this study was to evaluate apoptosis and parasite load in the liver and spleen of dogs with visceral leishmaniosis (VL), using immunohistochemistry. Liver and spleen samples from 71 dogs with VL were used. The parasite load in the spleen and liver showed significant difference between organs in infected group (P=0.0219). The density of the parasite load in the spleen (median=2.4) was higher than liver (median=0.8). Immunodetection of apoptotic cells was predominant in lymphocytes and differ between the infected and control group in spleen (P=0.0307) and liver (P=0.0346). There was a significant correlation between apoptosis and parasite load (P = 0.0084; r=0.3104) only in the spleen of the infected group, where it was observed that, when increasing the number of apoptotic cells increases the parasitic load. It was concluded that the liver and spleen of infected dogs presented greater numbers of cells undergoing apoptosis (lymphocytes) than the control group, thus suggesting that this process may be contributing towards the survival of Leishmania in these organs, because lymphocyte in apoptosis did not have the ability to present and recognize the antigen, allowing the survival of the parasite.
Influence of apoptosis on liver and spleen resistance in dogs with visceral leishmaniosis
Keywords: Apoptosis; Dogs; Immune escape; Leishmania infantum